Combination Therapy 1 (Dynamic Stretching & Cryotherapy) With Combination 2 (Dynamic Stretching & Massage) To Flexibility Hamstrings - Didik Purwanto; Ardiansyah D Kandupi; Khurotul Aini (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The purpose of this study was to test combination therapy 1 (dynamic stretching & cryotherapy) with a combination of 2 (dynamicstretches & massages) on hamstring flexibility. The method used is researchquasi experimental. The total sample participating in this study were 20 Untad female volleyball athletes. Samples were divided into two groups using the matching technique. Data collection used testsit and reach. Data analysis techniques in this study used statistics with the help of SPSS 25. From the results of the different test it can be seen that the t-count value in the combination group 1(dynamic stretching & cryotherapy) as big18,419, combination group 2(dynamicstretches & massages) as big23,400. The effect obtained from the value of p = 0.000 <0.05 which means combination therapy 1 (dynamic stretching & cryotherapy) with a combination of 2 (dynamicstretches & massages) increase the flexibility of the hamstring of Tadulako University women's volleyball athletes.